2018
DOI: 10.1016/j.ijcard.2018.06.089
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic substrate shift in human induced pluripotent stem cells during cardiac differentiation: Functional assessment using in vitro radionuclide uptake assay

Abstract: During in vitro cardiac maturation, we observed a metabolic shift to fatty acids, which are known as a main energy source of mammalian hearts, suggesting hi-PSC-CM as a potential functional phenotype to investigate alteration of cardiac metabolism in cardiac diseases. Results also highlight the use of available clinical nuclear medicine tracers as functional assays in stem cell research for improved generation of autologous differentiated cells for numerous biomedical applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…When hiPSCs exit pluripotency, they undergo metabolic remodeling so that energy production is converted to a mechanism that heavily relies on OxPhos and less on glycolysis (Moussaieff et al, 2015). The results of an in vitro tracer uptake study indicated a shift in the use of metabolic substrate from glucose to fatty acids after cardiac differentiation, which was similar to that observed in naturally isolated human cardiomyocytes (Nose et al, 2018).…”
Section: Introductionmentioning
confidence: 60%
“…When hiPSCs exit pluripotency, they undergo metabolic remodeling so that energy production is converted to a mechanism that heavily relies on OxPhos and less on glycolysis (Moussaieff et al, 2015). The results of an in vitro tracer uptake study indicated a shift in the use of metabolic substrate from glucose to fatty acids after cardiac differentiation, which was similar to that observed in naturally isolated human cardiomyocytes (Nose et al, 2018).…”
Section: Introductionmentioning
confidence: 60%
“…PSC-CMs also demonstrate a decrease in 18 F-FDG uptake relative to 125 I-BMIPP (fatty acid analog) uptake at 2 weeks of cardiomyocyte differentiation that increases further to at least week 8 of differentiation, indicating that PSC-CMs undergo a metabolic switch from using glucose to fatty acids during differentiation [50]. Standard media used for culture of PSC-CMs in vitro often has supraphysiologic levels of glucose (DMEM 4.5 g/L = 25 mM, DMEM/F12 31.5 g/L = 17.5 mM, RPMI 2 g/L = 11.1 mM glucose versus physiologic levels of~5.5 mM).…”
Section: Glucosementioning
confidence: 99%
“…Energy production in hiPSC-cardiomyocytes results from glycolysis and oxidative phosphorylation of mainly lactate (Hattori et al, 2010; Lopaschuk and Jaswal, 2010; Rana et al, 2012; Ellen Kreipke et al, 2016), while the primary source of energy in healthy mature cardiomyocytes originates from mitochondrial aerobic metabolism, being approximately 90% derived from fatty acid oxidation into acetyl-CoA prior to integration in the citrate cycle (Harris and Das, 1991; Opie, 2004a). Recent work has demonstrated the possibility to enhance the metabolic maturity of hiPSC-cardiomyocytes through induction of fatty acid metabolism (Hu et al, 2018; Nose et al, 2018; Ramachandra et al, 2018) and with 3D microenvironments that can enable increased contractile work (Correia et al, 2018; Ulmer et al, 2018). Such strategies can improve the use of hiPSC-cardiomyocytes to evaluate drug effects that mechanistically depend on metabolism.…”
Section: Increasing the Contractile Physiological Relevance Of Hipsc-mentioning
confidence: 99%